Analysis of diagnostic methods for peripheral arterial disease in patients with Diabetes mellitus (Research, Society and Development, 2023)
Objective: To synthesize information about the main methods for diagnosing obstructive arterial disease in patients with diabetes mellitus. Methodology: Integrative literature review aiming to answer the guiding question originated from the PICo strategy "How is the diagnosis of PAD in diabetic patients made?" based on articles selected from the MEDLINE/PubMed®, LILACS and WoS platforms. Results: For the diagnosis of obstructive arterial disease in diabetics, the main clinical method is the Ankle Brachial Index, which is a very advantageous technique for its sensitivity, easy execution and low cost. Also, among the laboratory methods, osteoprotegerin has high plasma levels in these patients; high brain natriuretic peptide is indicated as a predictor; and there is also omentin, which is useful for follow-up and severity assessment. Furthermore, as an imaging exam, angiography is the gold standard for this recognition, but it is an expensive and invasive method; on the other hand, Doppler ultrasound is a practical and effective tool to predict this form of vascular complication. Conclusion: It was possible to synthesize the main clinical and laboratory findings that can be examined during the care of patients with diabetes and that may be useful to detect PAD in these individuals. However, it is suggested that further studies be conducted to explore the new methods and their efficacy to enable early and efficient diagnosis.